Aplikasi Tasawuf pada Dunia Pendidikan Modern: APLIKASI TASAWUF PADA DUNIA PENDIDIKAN MODERN - Muchasan, Ali (Ali Muchasan, 2018)
The word sufism is indeed not in the Qur'an, but the substance and enthusiasm are clearly contained in it. Sufism is the teaching and belief that humans always want to achieve the purity of themselves and servants to be close to him who is most holy. Meanwhile Education contains an understanding of conscious and planned effort to make students have a mature personality and have maturity in thinking and acting. In reality, there are so many people who think that they enter their children in certain institutions to make them successful and have an established job and ignore personal attitudes that have maturity and good behavior. Sufism seeks to answer existing problems and existing patterns of thinking that Educational success is not seen from how well students finally have established jobs but more than that, that is to make students finally have a mature mindset and personality and have good skills.